An Analysis of Figurative Language in Autumn!S Album Golden Child, Chapter 3 - Kamarizki, Reynaldi; Wuryandari, Dyah Ambar (JEdu: Journal of English Education, 2023)
Figurative language refers to the use of expressive linguistic tools that transcend literal interpretation to convey deeper meanings and evoke vivid imagery. In light of this definition, this researchs objective is to find out the types of figurative language and to find out the most dominant type of figurative language in Autumn!'s album "Golden Child, Chapter 3" by utilizing Perrine's theory of figurative language. The researcher has employed the qualitative research method in this research. The researcher found 8 types of figurative language from 78 datum in this figurative research. It includes the following; Simile (18 datum), Metaphor (21 datum), Personification (3 datum), Synecdoche (5 datum), Metonymy (10 datum), Paradox (1 datum), Hyperbole (16 datum), and irony (4 datum). This research showed that the most dominant type of figurative language is Metaphor with 21 data.